Radiotherapy-induced changes in corneal morphology and biomechanics in myopathic thyroid eye disease - Wu, Pengsen; Rao, Jing; Yang, Shenglan; He, Xiaohan; Wu, Yuqing; Liu, Guiqin (Frontiers in Medicine, 2025)
PurposeTo assess differences in corneal morphology and biomechanics between patients with myopathic thyroid eye disease (TED) and normal controls (NCs), as well as to evaluate these changes following radiotherapy.MethodsPatients with active myopathic TED and age-, sex-, and spherical equivalent-matched NCs were enrolled in this study. All patients underwent radiotherapy and were followed up for 6 months post-treatment. Complete ophthalmic examinations were conducted for all subjects. Corneal morphology was evaluated using Pentacam, and biomechanics were assessed with Corvis ST tonometry, both before and 6 months post-radiotherapy.ResultsThis prospective, comparative clinical study involved 50 eyes from 50 TED patients and 30 eyes from 30 NCs. Post-radiotherapy, the intraocular pressure (IOP), proptosis, disease activity, diplopia, eye motility restriction and muscular index in TED patients significantly improved. Corneal morphological parameters such as elevation deviation, including back elevation (Db), pachymetric progression, relational thickness, overall deviation, and the index of surface variance, were significantly greater in TED patients compared to NCs, while Ambrosio’s Relational Thickness maximum was significantly lower. After radiotherapy, Db decreased, and posterior surface astigmatism increased with statistical significance. Significant biomechanical changes were observed in patients with TED after adjustment with biomechanically corrected IOP, including reduced A2 time and peak distance, increased tomographic and biomechanical index (TBI), as well as diminished maximum whole eye movement length (WEML). Post-radiotherapy, a significant increase in WEML was observed. Correlation analysis suggested that improvements in ocular biomechanics may be linked to reductions in IOP and proptosis.ConclusionPatients with myopathic TED demonstrated observable corneal alterations, including increased steepness, surface irregularity, reduced corneal hysteresis, and decreased orbital compliance. These biomechanical changes were associated with elevated TBI values, indicating heightened susceptibility to corneal ectatic disorders. Ocular biomechanical parameters may serve as as potential quantitative biomarkers for assessing treatment effectiveness in TED management.